Synthesis and characterization of nanosize CoxNi1-xFe2O4 powders by glycothermal process - Bae, DS; Kim, SW; Lee, HW; Han, KS (ELSEVIER SCIENCE BV, 2003)
Nanosized CoxNi1-xFe2O4 powders were prepared in ethylene glycol solution under mild temperature and pressure conditions by precipitation from metal nitrates. The average size and distribution of the synthesized CoxNi1-xFe2O4 powders was about 15 nm and narrow, respectively. The magnetic property of the synthesized CoxNi1-xFe2O4 powder was about 60 (emu/g) with superparamagnetic character at room temperature. (C) 2002 Elsevier Science B.V. All rights reserved.